Study of Bil-Uridine Diphosphate Glucuronyl Transferase (BILUDGPT- 1) Mutation in Neonatal Hyperbilirubinaemia with Glucose-6-Phosphate Dehydrogenase Deficiency. - Mohd Yusoff, Dr Narazah (Universiti Sains Malaysia, 2005)
Gilbert syndrome is caused by defects in the uridine diphosphate- glucuronosyltransferase 1A1 (UGT1A1) gene. These mutations differ among different populations and many of them have been found to be genetic risk factors for the development of neonatal jaundice.